Τιμές των μετοχών και ιδιοκτησιακό καθεστώς: μια διαστρωματική και διαχρονική ανάλυση - Καραθανάσης Γεώργιος Α.; Φίλιππας Νικόλαος Δ.; Χέβας Δημοσθένης (SPOUDAI Journal of Economics and Business, 2000)
Empirically our knowledge of the relation between firm performance and equity structure emanates from mainly USA and UK research papers. The paper investigates the relationship between share prices and institutional ownership of a sample of Greek companies quoted on the Athens Stock Exchange. The companies were observed from 1991 through 1996. The paper departs from earlier works in that it employs a specific valuation model. A further point of departure was the estimation of the relationship from a combination of cross section and time series data. The results did not show a significant relationship between share prices and institutional ownership. Tentatively it appears that institutional variables do not modify fundamental relationship advanced by finance theory. JEL Classification: G30, G32